Review on Health Concern: Trans Fatty Acids and Hydrogenation Process: Review: Trans Fatty Acids Impact on Human Health (Biological Sciences - PJSIR, 2024)
Trans fats are the worst fat that human being consumed in a diet. It has been produced during the hydrogenation process of edible oil/fats. Basically it has an adverse effect on human health by raising bad cholesterol (LDL) and decreasing the %level of good cholesterol (HDL). This ultimately increases the chance of heart stroke due to high build-up of bad cholesterol in blood arteries. Now days, the growing interest related to the consumption of foods products comprising trans fatty acids (TFAs) has been increased due to their risky effects on health. The permissible consumption limit of trans fat in foods should be less than 1%. Therefore, it is necessary to focuses on the process that generate TFAs in different food products. Hydrogenation is main source for TFAs production, the part of industrial hydrogenation is mainly affected to raise the level of trans fat (10-50%) comparative to thermal process (1-3%).